Georgian Military Road: Constant Communication (the Structure of “A Hero of Our Time” by M. Yu. Lermontov) - Dmitrovskaya, Maria (Literatūra, 2020)
The article demonstrates the fact that the duality of human consciousness is connected by mutual projections with the topography of the Georgian Military Road and the model of the universe and also forms the system of narrators / characters and the structure of the novel as a whole, including the number of stories and the partition of the novel into two parts. The sources used by the writer in the formation of the narrative structure of the novel are reconstructed. The numerological code of the novel is considered, the language bases of the conceptual system are analyzed. The embeddedness in the conceptual system of the trinomial name of Mikhail Yuryevich Lermontov is demonstrated. The vertical and horizontal spatial orientation of the Georgian Military Road allows discovering the topographic connection of the road with the dual reality of Lermontov, in which the opposite poles of good and evil, divine and evil turn into one.
Keywords: M. Yu. Lermontov; “А Hero of Our Time”; Georgian Military Road; conceptual system; problem of consciousnes; topography; narrative structure; model of the universe; numerological code; multilingual code